Pengaruh Tata Letak Sistem Irigasi Tetes Terhadap Distribusi Air - Akbar Fepria Anwar; Rusti; M. Agusalim; Fauzan Hamdi (Fakultas Teknik Universitas Muhammadiyah Parepare, 2026)
Drip irrigation system is one of the efficient and effective ways of using water, the use of drip irrigation system can increase Iand and plant productivity because the land can be planted throughout the year so that the planting index increases and cultivation activities do not depend on the rainy season. This study aims to determine the influence of variations in drip irrigation layout on water distribution and to determine the most efficient irrigation layout variations in water destribution. This method explains the scope of the study, time and place of the study, research tools and materials, research stages, and research flowcharts conducted. The results of the analysis show that the layout variation 1 with the highest level of efficiency is at Z 50 (EU%) reaching 98.98%. while the layout variation 2 with the highest level of efficiency is at S 50 (EU%) reaching 93.17% so layout variation 1 (zi-zag pattern) is superior to layout variation 2 so that the comparison of the most efficient drip irrigation layout variations is known.